Drp1-dependent mitochondrial fission mediates osteogenic dysfunction in inflammation through elevated production of reactive oxygen species - Zhang, Ling (PLoS One, 2017)
Although previous studies have implicated pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), to be detrimental for osteogenic activity, the related regulatory mechanisms are not yet fully validated. Since mitochondria host several essential metabolic processes and play a pivotal role in cellular functions, whether and how mitochondrial function contributes to inflammation-induced bone destruction needs further exploration. Our findings revealed that TNF-α impaired osteoblast function, including decreased mRNA levels of osteogenic markers, suppressed ALP expression and activity, and compromised cellular viability. Moreover, increased reactive oxygen species (ROS)-mediated oxidative stress in the TNF-α-treated group enhanced excessive mitochondrial fragmentation and disrupted mitochondrial function. However, treatment with antioxidant N-acetyl cysteine (NAC) or mitochondrial division inhibitor Mdivi-1 protected the cells from these adverse phenomena. These findings provide new insights into the role of the Drp1-dependent mitochondrial pathway in the osteogenic dysfunction during inflammation, indicating that this pathway may be a target for the development of new therapeutic approaches for the prevention and treatment of inflammation-induced bone destruction.